Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the problem of finding suitable functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] such that [tex]\( h(x) = (f \circ g)(x) = 5(x+1)^3 \)[/tex], let's break it down step-by-step.
Given:
[tex]\[ h(x) = 5(x + 1)^3 \][/tex]
We need to find functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] such that:
[tex]\[ h(x) = f(g(x)) \][/tex]
Let's examine the options provided:
### Option A:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = (x + 1)^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f((x + 1)^3) = 5((x + 1)^3)^3 \][/tex]
This simplifies to:
[tex]\[ f(g(x)) = 5(x + 1)^9 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
### Option B:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = x + 1 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(x + 1) = 5(x + 1)^3 \][/tex]
This simplifies to:
[tex]\[ f(g(x)) = 5(x + 1)^3 \][/tex]
This matches [tex]\( h(x) \)[/tex].
### Option C:
[tex]\[ f(x) = (x + 1)^3 \][/tex]
[tex]\[ g(x) = 5 x^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(5 x^3) = (5x^3 + 1)^3 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
### Option D:
[tex]\[ f(x) = x + 1 \][/tex]
[tex]\[ g(x) = 5 x^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(5 x^3) = 5x^3 + 1 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
Given the solutions above, only Option B is a valid combination of [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] that satisfies [tex]\( h(x) = 5(x + 1)^3 \)[/tex].
Therefore, one possibility for [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] is:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = x + 1 \][/tex]
Given:
[tex]\[ h(x) = 5(x + 1)^3 \][/tex]
We need to find functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] such that:
[tex]\[ h(x) = f(g(x)) \][/tex]
Let's examine the options provided:
### Option A:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = (x + 1)^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f((x + 1)^3) = 5((x + 1)^3)^3 \][/tex]
This simplifies to:
[tex]\[ f(g(x)) = 5(x + 1)^9 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
### Option B:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = x + 1 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(x + 1) = 5(x + 1)^3 \][/tex]
This simplifies to:
[tex]\[ f(g(x)) = 5(x + 1)^3 \][/tex]
This matches [tex]\( h(x) \)[/tex].
### Option C:
[tex]\[ f(x) = (x + 1)^3 \][/tex]
[tex]\[ g(x) = 5 x^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(5 x^3) = (5x^3 + 1)^3 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
### Option D:
[tex]\[ f(x) = x + 1 \][/tex]
[tex]\[ g(x) = 5 x^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(5 x^3) = 5x^3 + 1 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
Given the solutions above, only Option B is a valid combination of [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] that satisfies [tex]\( h(x) = 5(x + 1)^3 \)[/tex].
Therefore, one possibility for [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] is:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = x + 1 \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.